Current status for utilization of cold resistance genes and strategies in wheat breeding program - Ma, Shijie; Huang, Xiaorong; Zhao, Xiaoqing; Liu, Lilong; Zhang, Li; Gan, Binjie (Frontiers in Genetics, 2024)
Low temperature chilling is one of the major abiotic stresses affecting growth and yield of Triticum aestivum L. With global climate change, the risk of cold damage in wheat production has increased. In recent years, with the extensive research on wheat chilling resistance, especially the development of genetic engineering technology, the research on wheat chilling resistance has made great progress. This paper describes the mechanism of wheat cold damage, including cell membrane injury, cytoplasmic concentration increased as well as the imbalance of the ROS system. Mechanisms of cold resistance in wheat are summarised, including hormone signalling, transcription factor regulation, and the role of protective enzymes of the ROS system in cold resistanc . Functions of cloned wheat cold resistance genes are summarised, which will provide a reference for researchers to further understand and make use of cold resistance related genes in wheat. The current cold resistant breeding of wheat relies on the agronomic traits and observable indicators, molecular methods are lacked. A strategy for wheat cold-resistant breeding based on QTLs and gene technologies is proposed, with a view to breeding more cold-resistant varieties of wheat with the deepening of the research.